"Increasing Patient Loyalty: The Role Of Service Reliability, Brand Image, And Price With Integrity As The Key At The Executive Polyclinic Of Afiat PMI Bogor Hospital" - Dadang Ibrahim; Endang Ruswanti; Eri Yudhya Mulayani (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2024)
Business Aspects In the current era of globalization, hospital management is inevitable, this is also faced by PMI Bogor Hospital which is a class B private hospital located in the middle of Bogor City. Assessing the results of Google reviews until January 2024, PMI Hospital Bogor received a Rating rating of 3.7 out of 5.0, which means that the level of trust and patient satisfaction with PMI Bogor Hospital's services is still low. data on repeat visits of old patients at the Afiat polyclinic which reflects a cumulative decrease in patient loyalty, which is around 1-2% in 2023 compared to the previous year. The reliability of the service, brand image and price as well as integrity are suspected to be the causes. The research method used is quantitative descriptive with a cross sectional approach. The number of samples in this study was taken using a convenient sampling technique with a sample of 170 respondents. The data collection tool used used a questionnaire with a linkert scale. It was found that the increase in patient loyalty was indirectly positively influenced by brand image through service integrity as an intervention (indirect > direct estimation value; 0.284 > 0.171), and directly positively influenced by price (estimated value 0.663; P value 0.000) and Service Reliability (estimated value 0.170; P value 0.048) without going through integrity as an intervention. The conclusion of this study is that there is a significant positive influence between brand image variables that are influenced by integrity, but not on price and service reliability which directly have a positive effect on increasing patient loyalty without going through integrity variables